Pengaruh Sertifikasi Halal, Citra Merek, dan Harga terhadap Keputusan Pembelian Minuman Teh Botol Sosro (Studi Kasus pada Mahasiswa Pendidikan Tinggi Islamic Village) - Muizzudin Muizzudin; Siti Amelia Kisty (STES Islamic Village, 2020)
The purpose of this study was to explain the effect of Halal Certification, Brand Image and Price on the purchasing decision process of students to brand of Tea Bottles “Sosro” (Case Study at Islamic Village Higher Education). This research used quantitative methode. The population in this study were students who had or frequently consumed Sosro Bottle Tea products. Data collection was carried out by distributing questionnaires to 87 respondents. This research used multiple linear regression analysis method, with SPSS 25 software.The results showed that the Halal Certification and Brand Image had a positive and significant effect on the decision to buy “Sosro” tea bottles for Islamic Village Higher Education students, while the price had a positive and insignificant effect on the decision to purchase Teh Botol Sosro for Islamic Village Higher Education students, as well as certification. halal, Brand Image and Price simultaneously influenced the Purchase Decision of Sosro Bottled Tea Drink.